Valores de refer??ncia da densidade mineral ??ssea de universit??rios - Bezerra, Ricardo Fl??vio de Ara??jo (2003)
Inappropriate reference values for bone mineral density (BMD) may result in an incorrect diagnoses, erroneously classifying someone as normal, osteopenic or osteoporotic. Thus, the purpose of this study was to determine reference values (mean ?? standard deviation) for the lumbar spine (L2-L4) and proximal femur (femoral neck, trochanter, Ward??s triangle and total femur) of undergraduate students of the Catholic University of Brasilia (UCB). BMD of 117 (25 inactive and 92 active) men were measured aging 20 to 35 years using dual-energy X-ray absorptiometry (DXA). The BMD values (g/cm2) for each site were: L2-L4 - 1,24 ?? 00,16; femoral neck - 1,22 ?? 0,17; Ward??s triangle - 1,13 ?? 0,21; trochanter - 1,02 ?? 0,16; and total femur - 1,21 ?? 0,16. When comparing these BMD with DXA??s reference values the following T scores were respectively obtained: 0,03 ?? 1,30; 1,18 ?? 1,32; 1,28 ?? 1,62; 0,80 ?? 1,43; and 0,90 ?? 1,27. There were significant differences (p<0,001) between T scores based on DXA population and sample population at all femur sites, but not at lumbar spine (p=0,79). After comparing BMD and T scores of inactive and active students, significant differences were found in femur sites (p<0,01) but not at lumbar spine (p=0,05). The data suggest that people should have their BMD diagnosed based on their own population reference values and that there is an influence of physical activity on BMD VI.